Hubungan Kepatuhan Minum Obat Anti Hipertensi dengan Kualitas Hidup Pasien Hipertensi di Puskesmas Rawalo Kabupaten Banyumas - Damar Printinasari (Universitas Harapan Bangsa Purwokerto, 2023)
Hypertension is a cardiovascular disease which is a degenerative disease. Hypertension category with systolic blood pressure 140 mmHg or diastolic 90 mmHg. If this disease is not treated immediately, it can cause damage to blood vessels in the heart, brain. Compliance with taking medication is something that has an effect on controlling blood pressure. Quality of life is a benchmark in individuals to evaluate the level of well-being. The purpose of the study was to see if there was a relationship between adherence to antihypertensive medication and the quality of life of hypertensive patients at the Rawalo Health Center. The research used in this study is quantitative by using a descriptive correlation design with a cross sectional approach. The sampling method is purposive sampling with a sample of 76 respondents. Questionnaire using Modifed Morisky Scale and WHOQOL - BREFF with Chi Square test data analysis. The results showed that adherence to taking antihypertensive drugs was in the low category, namely 53.9% with moderate quality of life, namely 72.4%. The results of the analysis showed that there was a relationship between adherence to taking antihypertensive drugs and the quality of life of hypertensive patients at the Rawalo Health Center with p value = 0.003.